Concerning the debate about homocysteine, B vitamins, and dementia - Miller, Joshua W; McCaddon, Andrew; Yu, Jin-Tai; Hooshmand, Babak; Refsum, Helga; Smith, A David (Journal of Alzheimer's disease, 2025)
It is important to identify modifiable risk factors for dementia and to introduce policies to implement their modification. The Lancet Commission on Dementia Prevention, Intervention and Care failed to identify raised plasma homocysteine as a risk factor, despite considerable evidence; hence there is a need for a debate on this matter.